THE FACTORS DETERMINING PROFITABILITY OF GRAIN PRODUCTION IN A REGION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The research was conducted in order to determine influence of structural factors on profitability of grain production in the Altai Region, which is one of the main producers of grain in Russia. The influence of specialization and placement on the economic efficiency of grain production in the Altai Region was determined, factors for the formation of financial results and the financial condition of grain-type organizations were revealed. Comparison of agricultural organizations for which grain farming was the main production sector indicates that in case of increase in the cultivation area, the economic efficiency of resource use will be increased, despite higher costs per hectare of grain crops. The variation of organizations in the profitability of production is explained by the imperfection of the management system of the main branches in separate agricultural organizations, including non-optimal production volumes and placement in natural and economic zones. In the largest highly tailored organizations the economic efficiency of the resources used increased in the short-term perspective rose, but risks of its decline are created in the long-term period.